The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/bdrb.20315
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity testing for safety assessment: new approaches and technologies

Abstract: The ILSI Health and Environmental Sciences Institute's Developmental and Reproductive Toxicology Technical Committee held a 2-day workshop entitled "Developmental Toxicology-New Directions" in April 2009. The fourth session of this workshop focused on new approaches and technologies for the assessment of developmental toxicology. This session provided an overview of the application of genomics technologies for developmental safety assessment, the use of mouse embryonic stem cells to capture data on development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
(27 reference statements)
0
23
0
1
Order By: Relevance
“…Reproductive toxicology, including developmental toxicology, is a particularly difficult field as far as animal-to-human predictions are concerned (Knudsen et al, 2011;Makris et al, 2011). Reproductive toxicity aims to assess possible hazard to the reproductive cycle, with a high interest in the early stages of embryonic development (embryotoxicity).…”
Section: Reproductive Toxicitymentioning
confidence: 99%
“…Reproductive toxicology, including developmental toxicology, is a particularly difficult field as far as animal-to-human predictions are concerned (Knudsen et al, 2011;Makris et al, 2011). Reproductive toxicity aims to assess possible hazard to the reproductive cycle, with a high interest in the early stages of embryonic development (embryotoxicity).…”
Section: Reproductive Toxicitymentioning
confidence: 99%
“…Less than 5% of dossiers in the US EPA HPV database or the EU New Chemical Database (not public) contain any data in this field (Bremer et al, 2007a). Knudsen et al, have analyzed available data (Knudsen et al, 2011) …”
Section: Gov/iris/) This May Be Due To Other Effects Being More Sensmentioning
confidence: 99%
“…In order to move towards transcriptomics read-outs, PCR was employed to monitor specific gene expression (Pellizzer et al, 2004). Knudsen and colleagues (Knudsen et al, 2011) demonstrated the mEST's ability to capture data on disruption of developmental signaling pathways as a potential alternative for assessing developmental toxicity. "His example focused on the expression of genes for the 17 + 2 conserved signaling pathways critical to early development (National Research Council, 2000) The EC report (Adler et al, 2011) (cited literature there) gives a comprehensive overview on variants of the embryonic stem cell tests with respect "... to their readouts but also in the target cell differentiation (Peters et al, 2008;Zur Nieden et al, 2004).…”
Section: Reduction To Key Eventsmentioning
confidence: 99%
“…This is particularly intriguing given their small size, prolific reproductive capacity and ease of maintenance thus making it an ideal model for safety assessment of drugs de Esch et al, 2012;Knudsen et al, 2011). Moreover, detailed automatic and manual annotation provides evidence of more than 26,000 protein-coding genes, the largest gene set of any vertebrate so far sequenced, while comparison to the human reference genome shows that approximately 70% of human genes have at least one obvious zebrafish orthologue (Howe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%